a) сначала расписываем числитель.
+3х+2=0
находим дискриминант.
D =
- 4*1*(-2)=9
√9 = 3
х1=(1+3):2=2
х2=(1-3):2=-1
получаем: ![\frac{(x-2)+(x+1)}{x-2} \frac{(x-2)+(x+1)}{x-2}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-2%29%2B%28x%2B1%29%7D%7Bx-2%7D)
и в итоге, при сокращении получаем x+1
б) решаем по такому же принципу.
находим Дискриминант (D)
D=
- 4*2=1
= 1
х1=(-3+1):2=-1
х2=(-3-1):2=-2
получаем: ![\frac{(x+1)(x+2)}{x+1} \frac{(x+1)(x+2)}{x+1}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%2B1%29%28x%2B2%29%7D%7Bx%2B1%7D)
и в итоге, при сокращении получаем х+2